Miniaturized Ku-band transceiver based on 3D integration technology - Liu Haodong; Wu Hongjiang; Yu Xiaohui; Ma Zhangang (Dianzi Jishu Yingyong, 2022)
With silicon-based 3D integrated module and multilayer hybrid pressing printed circuit board(PCB) technique, a miniaturized Ku-band transceiver was designed, and meanwhile its principle project and approach were expounded. The transceiver employed 3D integrated structure. Radio frequency(RF) and intermediate frequency(IF) chips and their periphery circuits were integrated in 3D heterogeneous integrated module. Outer circuit board was made of a mixed-laminated multi-layer PCB. The transceiver used ball grid array(BGA) to connect 3D module and PCB. Signal transmission structure was optimized to reduce transmission loss and improve isolation among the channels. Product test indicates that the transceiver meet the requirements of inter-channel amplitude consistency, intra-band flatness, noise factor and other indicators. Besides, the transceiver has conformed to practical needs such as miniaturization, high integration, high consistency and high producibility.